Legitimacy Strategies in Corporate Environmental Reporting: A Longitudinal Analysis of German DAX Companies’ Disclosed Objectives - Borgstedt, Philipp (Journal of business ethics, 2019)
Ecological objectives in environmental reports usually promise a high degree of environmental responsibilities in a company’s activities. Several studies have already highlighted that most companies do not keep their promises since stakeholders’ expectations and a company’s capabilities for internal adjustments do not always match. Thus, a company might use strategic reporting in order not to endanger its legitimacy. However, no study so far has demonstrated how companies use different legitimacy strategies in reporting their environmental objectives over time. To achieve this in our study, we focus primarily on findings from legitimacy theory in combination with the legitimacy strategies suggested by Lindblom (in: Gray, Bebbington, Gray (eds) Social and environmental accounting: developing the field, Sage, Los Angeles, pp 51–63, 2010). To test our theoretical framework empirically, we analyze 260 corporate environmental reports of German DAX companies between the years 2000–2014 by coding all disclosed objectives within these reports. Based on this longitudinal approach, we are able to identify reporting patterns of the different companies that provide insights into those companies’ environmental reporting legitimacy strategies. Overall, this study contributes to research on voluntary disclosure by showing that a comprehensive analysis of the reporting pattern of disclosed objectives allows the identification of certain legitimacy strategies.